European sea bass (Dicentrarchus labrax) skin and scale transcriptomes - Pinto, Patricia IS (2019)
Fish skin and their appendages, the mineralized scales, are important organs for protection and homeostasis, but little is known about their specific transcript or protein repertoire. This study used RNA-seq to generate transcriptome data for skin and scales in the European sea bass (Dicentrarchus labrax), an important species for fisheries and aquaculture. RNA was extracted from the pectoral skin and from scales collected above the midline of immature one-year old sea bass. More than 20 x 10(6) reads were obtained for each tissue, using RNA-seq Illumina technology. De novo assembly resulted in 31,842 transcripts (of 500 base pairs or greater) for skin and 20,423 transcripts for scale. This dataset provides a useful resource for both aquaculture and fish conservation studies and for research into the physiology and molecular biology of fish skin and scales. (C) 2017 Elsevier B.V. All rights reserved.